Generation of authentication strings from graphic keys - Magalhães, Paulo Sérgio Tenreiro (2006)
The traditional authentication system used in technological applications is the well-known and widely spread user/password pair. This technology as proved itself as well acceptable by the users and quite safe when used according to good security practices, this is: frequent change of the password; use of letters, number and symbols in the password; not revealing the password to others; not using the same password in more then one service; etc. But this is not what really happens, so we need to improve the protocol. Graphical secrets present lots of advantages and can increase the level of security without a significant change in the users habits. For that, we need to possess strong ways to convert them into strings that will fed the implemented passwords systems. In this paper we present a method to do so.